Scaling Laws for Language Model Performance in Logical Reasoning Tasks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: What is the effect of model size on language model performance on logical reasoning tasks v14. 10 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.8/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.